Natural history of anorectal sepsis. Issue 13 (31st August 2017) - Sahnan, K.; Askari, A.; Adegbola, S. O.; Tozer, P. J.; Phillips, R. K. S.; Hart, A.; Faiz, O. D.
Abstract : Background: Progression from anorectal abscess to fistula is poorly described and it remains unclear which patients develop a fistula following an abscess. The aim was to assess the burden of anorectal abscess and to identify risk factors for subsequent fistula formation. Methods: The Hospital Episode Statistics database was used to identify all patients presenting with new anorectal abscesses. Cox regression analysis was undertaken to identify factors predictive of fistula formation. Results: A total of 165 536 patients were identified in the database as having attended a hospital in England with an abscess for the first time between 1997 and 2012. Of these, 158 713 (95·9 per cent) had complete data for all variables and were included in this study, the remaining 6823 (4·1 per cent) with incomplete data were excluded from the study. The overall incidence rate of abscess was 20·2 per 100 000. The rate of subsequent fistula formation following an abscess was 15·5 per cent (23 012 of 148 286) in idiopathic cases and 41·6 per cent (4337 of 10 427 in patients with inflammatory bowel disease (IBD) (26·7 per cent coded concurrently as ulcerative colitis; 47·2 per cent coded as Crohn's disease). Of all patients who developed a fistula, 67·5 per cent did so within the first year. Independent predictors of fistula formation were: IBD, in particular Crohn's disease (hazard ratio (HR) 3·51; P < 0·001), ulcerative colitis (HR 1·82; P < 0·001), female sex (HR 1·18; P < 0·001), age at time of first abscess 41–60 years (HR 1·85 versus less than 20 years; P < 0·001), and intersphincteric (HR 1·53; P < 0·001) or ischiorectal (HR 1·48; P < 0·001) abscess location compared with perianal. Some 2·9 per cent of all patients presenting with a new abscess were subsequently diagnosed with Crohn's disease; the median time to diagnosis was 14 months. Conclusion: The burden of anorectal sepsis is high, with subsequent fistula formation nearly three times more common in Crohn's disease than idiopathic disease, and female sex is an independent predictor of fistula formation following abscess drainage. Most fistulas form within the first year of presentation with an abscess. Abstract : Women more likely to develop fistula